PENERAPAN MODEL PEMBELAJARAN MIND MAPPING DENGAN GAMBAR SERI UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS V SD NEGERI 5 KEBUMEN TAHUN AJARAN 2015/2016 - Rina, Rina (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Mind Mapping Learning Model Using Serial Pictures in Improving Social Science Learning Outcomes for the Fifth Grade Students of SD Negeri 5 Kebumen in the Academic Year of 2015/2016. The objectives of this research are to describe the application of mind mapping learning model using serial pictures and to improve social science learning outcomes. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles in five meetings. Each cycle consisted of planning, action, observation, and reflection. Source of data were derived from students, teachers, and documents. Techniques of collecting data were learning outcomes test, observation, and interview. The results of this research showed that there are nine stages of mind mapping learning model using serial pictures, namely: (1) the delivery of learning objectives; (2) the delivery of learning material by using pictures and notes; (3) group division; (4) the determination of the central ideas with pictures; (5) the determination of ideas related to the central idea of the pictures; (6) connecting the central idea with the idea of each image in the form of a curved line; (7) presentation of results of group discussions; (8) reinforcement and conclusions; and (9) closing. In addition, the social science learning outcomes improved significantly.Keywords: mind mapping, serial pictures, learning outcomes, social science Abstrak: Penerapan Model Pembelajaran Mind Mapping dengan Gambar Seri untuk Meningkatkan Hasil Belajar IPS pada Siswa Kelas V SD Negeri 5 Kebumen Tahun Ajaran 2015/2016. Penelitian ini bertujuan untuk mendeskripsikan penerapan model pembelajaran mind mapping dengan gambar seri dan meningkatkan hasil belajar IPS. Penelitian tindakan kelas kolaboratif ini dilaksanakan dalam tiga siklus dengan lima kali pertemuan. Sumber data berasal dari siswa, guru, dan dokumen. Teknik pengumpulan data menggunakan tes, observasi, dan wawancara. Hasil penelitian ini menunjukkan bahwa terdapat sembilan langkah model pembelajaran mind mapping dengan gambar seri yaitu: 1) penyampaian tujuan; 2) penyampaian materi dengan gambar dan pencatatan; 3) pembentukan kelompok; 4) penentuan ide sentral dengan gambar; 5) penentuan gagasan sebagai ide sentral dengan gambar; 6) penghubungan ide sentral dengan gagasan setiap gambar menggunakan garis lengkung; 7) presentasi hasil diskusi; 8) penguatan dan kesimpulan; dan 9) penutup, dan hasil belajar IPS meningkat.Kata kunci: mind mapping, gambar seri, hasil belajar, IPS